Quo Vadis Modern Salafism: Re-Questioning Salafi's Moderation Value on Social Media - Arisy Abror Dzukroni; Muhammad Tareh Aziz (Fakultas Ushuluddin, Adab dan Humaniora (FUAH) UIN Kiai Haji Achmad Siddiq Jember, 2023)
This study examines the value of religious moderation in the Salafi movement on social media in Indonesia. The label of radical movement attached to the Salafi group has been considered a threat to the country's integrity. Their propaganda and schooling, especially on social media, contain some content that will cause social separation. The government mainstreams the campaign for religious moderation to counter radicalism. Hence, several organizations have been dissolved by the government because they are considered dangerous. However, the question is whether all groups linked to Salafi are hazardous and threaten the country's integrity. This article will solve this question using qualitative descriptive research. This research is equipped with a content analysis method. The results found three variants of the Salafi group spread in social media. The three variants are purist, haraki, and jihadist. The three variants have their style, even though purificating Islamic thought is the starting point of their agenda. By referring to the religious moderation indicators by the Ministry of Religious Affairs (nationalism, tolerance, non-violence, and accommodative to local culture), it can be concluded that: First, not all Salafi groups commit acts of violence; Second, not all Salafi groups are anti-nationalism; Third, several Salafi groups have moderate values in their teachings even though they can not be considered as moderate groups.